Production of Al-Mg alloy Ribbons by Using Single Roller Wheel Melt Spinning as a Non-Conventional Forming Technology. - Jassim, Ahmad. K.; thin, similar technology used to produce near-net shaper; Hammood, Ali S. (Basrah Journal for Engineering Sciences, 2014)
Single roll melt spinning is a non-conventional forming process used to produce rapidly solidified thin ribbons as a near net shaper by direct casting from liquid state. In this paper, single roll made from brass with a diameter of 150 mm was used to produce rapidly solidified Al-Mg alloys ribbons. The ribbons are produced with thickness in the range of 20 to 330 µm. The results exhibited unique advantages in refining the microstructure, and modifying the mechanical properties of these ribbons. The hardness was improved to about twice the original hardness of alloy. Moreover, corrosion resistance of alloy was improved and their rate was redcued from 10.02 to 1.643 mpy for alloy type 5052 and from 6.91 to 1.943 mpy for 5083.